PEMBERDAYAAN EKONOMI IBU PKK MELALUI GALERI BANK SAMPAH DAN URBAN FARMING MENUJU PEMBANGUNAN LINGKUNGAN BERKELANJUTAN DI KAMPUNG MERGOSONO - Fawwaz, Muhammad Iqbal; Akbar, Muhammad Fikri; Churiyah, Madziatul; Sholikhan (Transpublika Publisher, 2023)
Waste management is a pressing concern in urban areas, and one effective solution is the establishment of a waste bank. In Kampung Mergosono, addressing waste issues involves active participation from the PKK (Family Welfare Movement) mothers. The goal is to educate and empower the community in waste management, fostering social awareness and behavior change through the